Non-invasive predictors of the first episode of bleeding from esophageal varices in patients with liver cirrhosis awaiting transplantation - V. L. Korobka; Yu. V. Khoronko; V. D. Pasechnikov; R. V. Korobka; M. V. Malevanny; E. S. Pak; D. V. Pasechnikov (Трансплантология (Москва), 2024)
Background. To date, various non-invasive techniques or tests have been proposed that can identify a high risk of bleeding from esophageal varices. Despite a significant number of studies revealing the presence of venous varices as a likely factor for the development of bleeding due to their rupture, data on predictors of the first episode of bleeding are few and often contradictory.Objective. To determine non-invasive independent predictors of the first episode of bleeding in patients waiting for liver transplantation.Material and methods. A comparative retrospective study was conducted in 729 patients with decompensated cirrhosis who were on the waiting list for liver transplantation. We analyzed demographic, clinical and laboratory parameters, MELD-Na, Child-Turcotte-Pugh scores, FIB-4 Index, APRI, AST/ALT ratio; we determined the liver stiffness, spleen diameter, studied the liver stiffness-spleen diameter to platelet ratio risk score (LSPS model), platelet count/spleen diameter ratio in the groups of patients with the first episode of bleeding (n=334) and without it (n=395). The accumulated risks in the compared groups were assessed using a model of proportional hazards (Cox regression) in univariate and multivariate analysis.Results. During 48 months of follow-up from the time of patient placement on the liver transplant waiting list, primary bleeding events developed in 45.8%. The risk of developing the first episode of bleeding progressively increased with LSPS >3.5 and reached maximum values in patients awaiting liver transplantation within 48 months of inclusion in the waiting list, while with LSPS <3.5 the risk was minimal.Conclusion. Independent non-invasive predictors of the first episode of bleeding are a high level of AST, a high fibrosis index (FIB-4), a decrease in the ratio of platelet count/spleen diameter and a high LSPS value. Their application in clinical practice will improve the results of dispensary and screening examinations of patients with portal hypertension.